The level of TACI gene expression in myeloma cells is associated with a signature of microenvironment dependence versus a plasmablastic signature - Moreaux, Jérôme; Cremer, Friedrich Walter; Reme, Thierry; Raab, Marc-Steffen; Mahtouk, Karene; Kaukel, Philine; Pantesco, Veronique; De Vos, John; Jourdan, Eric; Jauch, Anna; Legouffe, Eric; Moos, Marion; et al. (Blood, 2005)
B-cell activating factor (BAFF) and a proliferation-inducing ligand (APRIL) have been shown to promote multiple myeloma (MM) cell growth. We show that the main site of production for BAFF and APRIL is the bone marrow (BM) environment, and that production is mainly by monocytes and neutrophils. In addition, osteoclasts produce very high levels of APRIL, unlike BM stromal cells. Myeloma cells (MMCs) express TACI (transmembrane activator and calcium modulator and cyclophilin ligand interactor), the receptor of BAFF/APRIL, at varying levels. TACI expression is a good indicator of a BAFF-binding receptor. Expression data of purified MMCs from 65 newly diagnosed patients have been generated using Affymetrix microarrays and were analyzed by supervised clustering of groups with higher (TACIhi) versus lower (TACIlo) TACI expression levels. Patients in the TACIlo group had clinical parameters associated with bad prognosis. A set of 659 genes was differentially expressed between TACIhi and TACIlo MMCs. This set makes it possible to efficiently classify TACIhi and TACIlo MMCs in an independent cohort of 40 patients. TACIhi MMCs displayed a mature plasma cell gene signature, indicating dependence on the BM environment. In contrast, the TACIlo group had a gene signature of plasmablasts, suggesting an attenuated dependence on the BM environment. Taken together, our findings suggest using gene expression profiling to identify the group of patients who might benefit most from treatment with BAFF/APRIL inhibitors.